Efektivitas Pengawasan Partisipatif Dinas Kebersihan Lingkungan Hidup Dalam Pengawasan Pencemaran Sungai di Kabupaten Aceh Tenggara - Naja, Ahlul (Universitas Muhammadiyah Sumatera Utara, 2023)
This study aims to determine the effectiveness of participatory supervision of the environmental hygiene service in monitoring river pollution carried out by the Southeast Aceh Environmental Agency in overcoming environmental pollution. And to find out the mitigation of river pollution carried out by the Southeast Aceh Environment Agency. This research method uses a descriptive method with qualitative analysis, namely a problem-solving procedure that is investigated by observing a state of the research object at the present time based on visible facts or as it is the success rate in the implementation of the supervisory function of the Southeast Aceh Environmental Agency has not been effective enough. This ineffectiveness is evident from not meeting the SOP even though it is in accordance with the plan. And the goals and objectives determined to involve the role of the community are still the lack of notification and information conveyed so that the community knows and participates in the activities carried out.